2010
DOI: 10.1096/fj.09-150359
|View full text |Cite
|
Sign up to set email alerts
|

High‐molecular‐weight β‐amyloid oligomers are elevated in cerebrospinal fluid of Alzheimer patients

Abstract: There is accumulating evidence that soluble amyloid-beta (Abeta) oligomers, rather than amyloid fibrils, are the principal pathogenic species in Alzheimer disease (AD). Here, we have developed a novel enzyme-linked immunosorbent assay (ELISA) specific for high-molecular-weight (HMW) Abeta oligomers. Analysis of Abeta oligomers derived from synthetic Abeta 1-42, by size-exclusion chromatography (SEC), revealed that our ELISA specifically detected HMW Abeta oligomers of 40-200 kDa. Using this ELISA, we detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
190
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(205 citation statements)
references
References 54 publications
12
190
2
1
Order By: Relevance
“…The BAN50 SAS-ELISA has been shown to specifically detect high molecular weight Ab oligomers in CSF samples from patients with AD or mild cognitive impairment; these signals are significantly higher than those obtained from age-matched controls, as well as correlating negatively with scores obtained in the MMSE. These results indicate a possible role for the SAS-ELISA as a useful molecular diagnostic marker for AD, and perhaps a surrogate marker for disease severity [92]. Again, there is a real possibility to combine such endpoints with reagent-free spectrochemical endpoints; in fact, these latter technologies could allow for real-time measurements of emerging pathology, a major challenge in neurodegenerative disease.…”
Section: Neurodegenerationmentioning
confidence: 97%
“…The BAN50 SAS-ELISA has been shown to specifically detect high molecular weight Ab oligomers in CSF samples from patients with AD or mild cognitive impairment; these signals are significantly higher than those obtained from age-matched controls, as well as correlating negatively with scores obtained in the MMSE. These results indicate a possible role for the SAS-ELISA as a useful molecular diagnostic marker for AD, and perhaps a surrogate marker for disease severity [92]. Again, there is a real possibility to combine such endpoints with reagent-free spectrochemical endpoints; in fact, these latter technologies could allow for real-time measurements of emerging pathology, a major challenge in neurodegenerative disease.…”
Section: Neurodegenerationmentioning
confidence: 97%
“…Several years later, Georganopoulou et al [5] used monoclonal and polyclonal antibodies specific for so called amyloid-derived diffusible ligands (ADDLs): the detection of the immune-reaction product was amplified using a nanoparticle-based biobarcode assay to demonstrate that ADDLs (molecular weights between 17 and 42 kDa) are elevated significantly in AD patients compared to age-matched controls. Fukumoto et al [6] developed a novel enzyme-linked immunosorbent assay and demonstrated elevated levels of high molecular weight (HMW) Aβ oligomers of 45-to 90-KDa in the CSF of AD patients. Such HMW oligomers account however for a very small amount (<1%) of the total oligomer mixture in the CSF of AD patients, which is instead predominantly composed of low molecular weight (LMW) oligomers [6].…”
mentioning
confidence: 99%
“…Fukumoto et al [6] developed a novel enzyme-linked immunosorbent assay and demonstrated elevated levels of high molecular weight (HMW) Aβ oligomers of 45-to 90-KDa in the CSF of AD patients. Such HMW oligomers account however for a very small amount (<1%) of the total oligomer mixture in the CSF of AD patients, which is instead predominantly composed of low molecular weight (LMW) oligomers [6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, extensive investigation of the aggregation pathway reveals that oligomeric assemblies and not mature fibrils are responsible for Aβ neurotoxicity (4)(5)(6)(7)(8)(9). Several approaches have been designed to target the Aβ assembly process in an effort to reduce toxic species in the brain.…”
mentioning
confidence: 99%